Prasugrel - Gianluca Airoldi (Italian Journal of Medicine, 2013)
Antiplatelet drugs are the cornerstone of treatment for patiens with Acute Coronary Syndromes (ACS) undergoing percutaneous coronary intervention. Clopidogrel and aspirin improve longterm vascular clinical outcomes in these patients and have become a standard of care. However, many patients still experience ischemic/thrombotic events due to potential insufficient platelet inhibition. Prasugrel is a novel third-generation oral thienopyridine analog with a structure similar to that of clopidogrel and ticlopidine. Like the other thienopyridines, prasugrel is a pro-drug requiring hepatic metabolism to its active form to inhibit platelet aggregation induced by Adenosine Diphosphate (ADP) by irreversibly binding to the ADP purinergic receptor (P2Y12) on the platelet surface. Laboratory results with prasugrel support more potent antiplatelet effects, a lower interpatient variability in antiplatelet response, and a reduced time to onset of antiplatelet activity compared with clopidogrel, even when clopidogrel is administered at doses higher than the currently approved 300-mg loading dose and 75-mg/day maintenance dose. These differences may have mainly a pharmacokinetic basis.While the active metabolites of prasugrel and clopidogrel show similar levels of platelet inhibitioninvitro, theamount of eachactivemetabolite generatedinvivomaybequite different, expecially in some substet of patients (e.g., the so called ‘‘CYP2C9 poor metabolizers’’). However, it is not yet clear whether these pharmacologic improvements can translate to clinical benefits. The results of the large TRITON-TIMI 38 trial, which compared prasugrel and clopidogrel in patients with acute coronary syndrome who were scheduled to receive coronary stents, demonstrated a significant reduction in ischemic events with prasugrel, although this was associated with a greater risk of bleeding. More studies with prasugrel should determine its optimal dosage regimen to minimize bleeding risks and evaluate its outcomes in ACS in varius subset of patiens. The exact role of prasugrel in the management of coronary heart disease remains to be defined.